Location as a Factor in the Prediction of Psychomotor Performance in Automobile Engine using Computer Simulation - Ibezim, Nnenna Ekpereka (Advances in Social Sciences Research Journal, 2016)
This study compared two groups of four technical college classes studying automobile engine. One group of two schools is located in rural area and the other group, also from two schools, is located in urban area. They learned automobile engine using computer simulation based on a dynamic, three-dimensional model of automobile engine. The study adopted a pretest, posttest, control group, quasi-experimental research design. There were three weeks (of 45 minutes each) of treatment for the study. Psychomotor rating scale was used to obtain data. The area of the study is Enugu State of Nigeria. 526 NTC 1 (average of 16-17 years old) students of Motor Vehicle Mechanics’ Work formed the population of the study; while 106 students were sampled from 4 schools out of the 22 schools managed by Science Technical and Vocational Schools Management Board (STVSMB), Enugu. Arithmetic mean was utilised to answer the research question, while the hypothesis was tested using Analysis of Covariance (ANCOVA) tested at .05 level of significance. The study found that the effect of computer simulation teaching technique on students’ psychomotor performance in automobile engine is greater in urban students than in rural students. It was also found that the difference was not significant. Based on the findings, one of the recommendations made is that since urban students performed better than the rural students, the rural students should be guided properly in order to maximize their academic potentialities.